Pengaruh Investasi dan Tenaga Kerja terhadap Pendapatan Provinsi melalui Pertumbuhan Ekonomi di Sumatera Utara (2001-2021) - Brigita Zai; Nadia Vega Surbakti; Natalia Natalia (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study examines the influence of investment and labor on provincial income using the economic growth of North Sumatra Province from 2001 to 2021. This research is based on the importance of investment and labor as a crucial component of economic growth and increasing regional income. This study uses a quantitative approach and path analysis. Documentary data were obtained from the Central Statistics Agency (BPS) and the Ministry of Investment/BKPM. The data obtained were tested through two substructures: the influence of economic growth and investment on provincial income and the influence of economic growth, labor, and investment on provincial income. The results indicate that economic growth is positively and significantly influenced by investment and labor, and economic growth is positively and significantly influenced by both, as well as provincial income, simultaneously. Although economic growth facilitates the relationship between labor and provincial income, this relationship is not fully mediated by it. The results of this study indicate that strengthening the quality of the labor force and productive investment plays a crucial role in accelerating inclusive and sustainable economic growth while strengthening the effectiveness of regional policies in achieving income equality in North Sumatra Province.